A review of hydrogen-air cloud explosions: The fundamentals, overpressure prediction methods, and influencing factors. (29th April 2023) - Hu, Qingchun; Zhang, Xihong; Hao, Hong
Abstract: Hydrogen is one of the most promising renewable energies that has been observing rapid development over the past years. Recent accidental explosion incidents and the associated damages have demonstrated the importance of hydrogen safety against potential explosions. This article presents a systematic review on hydrogen explosions. Potential explosion scenarios including the existence of impurities and rich-oxygen environment in the production, storage with extreme-high pressure and ultra-low temperature, transportation, and consumption processes are reviewed. Different types of hydrogen-air cloud explosion include expansion and deflagration, detonation, and deflagration-to-detonation transition (DDT). Existing studies on hydrogen explosion covering laboratory and field blasting test, numerical simulation utilizing various computational approaches, and theoretical derivation are reviewed and summarized. CFD modeling is currently one of the main research methods because of its cost effectiveness, though challenges existing in simulation hydrogen-air cloud detonation comparing with testing results. Apart from the properties of hydrogen-air cloud such as concentration, size and heterogeneity, environmental factors such as ignition, ventilation and obstacle are found to strongly influence the loading characteristics of hydrogen-air cloud explosion. Existing prediction approaches for estimating blast loading from hydrogen-air cloud explosion including the TNT equivalent method (TNT-EM), TNO multi-energy method (TNO MEM), and Baker-Strehlow-Tang method (BST) are primarily empirical based. Because of the inherited difference of hydrogen-air cloud from solid explosives and conventional flammable gases, the accuracies of these approaches are still doubtable, which requires further study. Highlights: The fundamentals and potential scenarios of hydrogen explosions are reviewed. Different hydrogen explosions and overpressure prediction methods are summarized. Critical factors affecting the overpressure time histories are examined. The gaps and the future developments of hydrogen explosions are proposed.